An international survey on patterns of practice in NAFLD and expectations for therapies—The POP‐NEXT project. Issue 6 (26th April 2022) - Ratziu, Vlad; Anstee, Quentin M.; Wong, Vincent Wai‐Sun; Schattenberg, Jörn M.; Bugianesi, Elisabetta; Augustin, Salvador; Gheorghe, Liana; Zambon, Vittoria; Reau, Nancy
Abstract: Background and Aims: Differences between countries in NAFLD patient care pathways and management need to be understood prior to defining supranational guidelines. Approach and Results: We conducted an anonymous survey in France, Germany, Hong Kong, Italy, Romania, Spain, the United Kingdom, and the United States among physicians providing specialist care for patients with NAFLD. Modalities of patient referral, patterns of practice (diagnosis, staging, monitoring, and indications for liver biopsy), therapeutic management, and expectations for future NASH pharmacotherapies were assessed, with 664 physicians completing the survey. Referral to surveyed physicians (SPs) mostly came from primary care. Prior to referral, NAFLD was rarely diagnosed, and noninvasive tests were not performed. Screening for comorbidities by SPs was incomplete and cardiovascular risk not calculated. Elastometry in combination with a serum biomarker was the most common first‐line method for fibrosis staging. Liver biopsy, when performed, was often delayed by at least 1 year after diagnosis. It was, however, recommended even if noninvasive methods indicated advanced fibrosis. Frequent, biannual monitoring was conducted, including HCC surveillance in Stage 3 fibrosis. SPs rarely implemented and followed dietary and lifestyle changes themselves, and local availability of such programs was highly heterogenous. SPs favored pharmacotherapy based on mechanism of action adapted to the stage of the disease, including for early stages such as steatohepatitis with mild fibrosis. Conclusions: This international survey revealed major deficiencies and delays in referral pathways, suboptimal screening for comorbidities or managing of lifestyle modifications by SPs, and limited local availability for nonpharmacological interventions. Monitoring practices are not aligned with current guidelines. Abstract : image